Effective polyclonal antibodies against the virulence-associated protein D (VapD) of Helicobacter pylori, obtained from recombinant VapD - Alejandro Flores-Alanis; Gabriela Delgado; Carlos Santiago-Olivares; Víctor Manuel Luna-Pineda; Armando Cruz-Rangel; Denilson Guerrero-Mejía; María Luisa Escobar-Sánchez; Nayeli Torres-Ramírez; Rosario Morales-Espinosa (PLoS ONE, 2025)
Helicobacter pylori is a microorganism associated with serious gastric pathologies. This bacterium presents specific genes that encode for different virulence factors associated with the development of gastric disease. The VapD protein has rarely been studied, although it has been previously demonstrated its participation in the protection of Helicobacter pylori within gastric cells. In the present work, we document the protocols developed to generate the VapD recombinant protein and the subsequent production of polyclonal antibodies. Our research group faced several problems throughout the trials; however, all of them were successfully solved.